Parametric Matching of Drivetrain For Parallel Hybrid Electric Vehicle - Zhang Zhongwei; Yu Hao; Li Yingli (Institute of Advanced Engineering and Science, 2013)
Based on the software ADVISOR2002, the simulation modal of the assembly power and vehicle of the Parallel Hybrid Electric Vehicle(PHEV)has been set up.With the control targets for power characteristic and for fuel characteristic, this paper still considers the state of charge meanwhile; this thesis presents a simulation analysis of the PHEV and the influence on vehicle characteristic by component parameters of drivetrain, and studies the parametric choice and proper parametric matching among drivetrain component. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3408